Associations between sleep parameters, non-communicable diseases, HIV status and medications in older, rural South Africans - Gómez-Olivé, F. Xavier; Rohr, Julia K.; Roden, Laura C.; Rae, Dale E.; von Schantz, Malcolm (Nature Research, 2018)
As part of the Health and Aging in Africa: A Longitudinal Study of an INDEPTH Community in South Africa (HAALSI), we investigated sleep habits and their interactions with HIV or non-communicable diseases (NCDs) in 5059 participants (median age: 61, interquartile range: 52—71, 54% females). Selfreported sleep duration was 8.2±1.6h, and bed and rise times were 20:48±1:15 and 05:31±1:05 respectively. Ratings of insufcient sleep were associated with older age, lack of formal education, unemployment, and obesity (p<0.05). Ratings of restless sleep were associated with being older, female, having more education, being unemployed, and single. Hypertension was associated with shorter self-reported sleep duration, poor sleep quality, restless sleep, and periods of stopping breathing during the night (p<0.05). HIV positive individuals not on antiretroviral treatment (ART) reported more nocturnal awakenings than those on ART (p=0.029) and HIV negative individuals (p=0.024), suggesting a negative net efect of untreated infection, but not of ART, on sleep quality. In this cohort, shorter, poor-quality sleep was associated with hypertension, but average self-reported sleep duration was longer than reported in other regions globally. It remains to be determined whether this is particular to this cohort, South Africa in general, or low- to middle-income countries undergoing transition.
Keywords: Sleep parameters; Non-communicable diseases; HIV status; Rural South Africa; Aging; SDG-3: Good health and well-being